Severe Pneumonia Caused by Coinfection With Influenza Virus Followed by Methicillin-Resistant Staphylococcus aureus Induces Higher Mortality in Mice - Jia, Leili; Zhao, Jiangyun; Yang, Chaojie; Liang, Yuan; Long, Pengwei; Liu, Xiao; Qiu, Shaofu; Wang, Ligui; Xie, Jing; Li, Hao; Liu, Hongbo; Guo, Weiguang; et al. (Frontiers in Immunology, 2019)
Background: Coinfection with influenza virus and bacteria is a major cause of high mortality during flu pandemics. Understanding the mechanisms behind such coinfections is of utmost importance both for the clinical treatment of influenza and the prevention and control of epidemics. Methods: To investigate the cause of high mortality during flu pandemics, we performed coinfection experiments with H1N1 influenza virus and Staphylococcus aureus in which mice were infected with bacteria at time points ranging from 0–7 days after infection with influenza virus. Results: The mortality rates of mice infected with bacteria were highest 0–3 days after infection with influenza virus; lung tissues extracted from these co-infected mice showed higher infiltrating cells and thicker lung parenchyma than lung samples from coinfected mice in which influenza virus was introduced at other times and sequences. The levels of interferon (IFN)-γ, tumor necrosis factor (TNF)-α, interleukin (IL)-8, and IL-6 in the 0–3-day coinfected group were significantly higher than those in the other groups (p<0.01), as were the mRNA levels of IFN-γ, IL-6, and TNF-α. Coinfection with influenza virus and S. aureus led to high mortality rates that are directly dependent on the sequence and timing of infection by both pathogens. Moreover, coinfection following this particular schedule induced severe pneumonia, leading to increased mortality. Conclusions: Our data suggest that prevention of bacterial co-infection in the early stage of influenza virus infection is critical to reducing the risk of clinical mortality.